Interdecadal Variability of the East Asian Winter Monsoon and Its Possible Links to Global Climate Change - 丁一汇 柳艳菊 梁苏洁 马晓青 张颖娴 司东 梁萍 宋亚芳 张锦 (Acta meteorologica Sinica, 2014)
This paper presents a concise summary of the studies on interdecadal variability of the East Asian winter monsoon （EAWM） from three main perspectives. （1） The EAWM has been significantly affected by global climate change. Winter temperature in China has experienced three stages of variations from the beginning of the 1950s： a cold period （from the beginning of the 1950s to the early or mid 1980s）, a warm period （from the early or mid 1980s to the early 2000s）, and a hiatus period in recent 10 years （starting from 1998）. The strength of the EAWM has also varied in three stages： a stronger winter monsoon period （1950 to 1986/87）, a weaker period （1986/87 to 2004/05）, and a strengthening period （from 2005）. （2） Corresponding to the interdecadal variations of the EAWM, the East Asian atmospheric circulation, winter temperature of China, and the occurrence of cold waves over China have all exhibited coherent interdecadal variability. The upper-level zonal circulation was stronger, the mid-tropospheric trough over East Asia was deeper with stronger downdrafts behind the trough, and the Siberian high was stronger during the cold period than during the warm period. （3） The interdecadal variations of the EAWM seem closely related to major modes of variability in the atmospheric circulation and the Pacific sea surface temperature. When the Northern Hemisphere annular mode/Arctic Oscillation and the Pacific decadal oscillation were in negative （positive） phase, the EAWM was stronger （weaker）, leading to colder （warmer） temperatures in China. In addition, the negative （positive） phase of the Atlantic multi decadal oscillation coincided with relatively cold （warm） temperatures and stronger （weaker） EAWMs. It is thus inferred that the interdecadal variations in the ocean may be one of the most important natural factors influencing long-term variability in the EAWM, although global warming may have also played a significant role in weakening the EAWM.